2012
DOI: 10.1039/c2jm31384g
|View full text |Cite
|
Sign up to set email alerts
|

Versatile fabrication of nanoscale sol–gel bioactive glass particles for efficient bone tissue regeneration

Abstract: There has been an increased interest in developing nanoscale biomaterials for bone tissue regeneration, due to the biomimetic nano-dimensions and properties compared to natural tissue (bone). Bioactive glass (BG) is regarded as an excellent biomaterial for use in bone regeneration, because of its bioactivity and osteoconductivity. Here, we develop bioactive glass nano-scale particles (NBGs) by sol-gel combining gelation-induced phase separation technology, and demonstrate the effect of bioactive glass dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 35 publications
(66 reference statements)
2
55
0
1
Order By: Relevance
“…Furthermore, using sol-gel methodology sub-micron bioactive glass particles (85% SiO 2 , 15% CaO) with a mean particle size of 250 nm demonstrated significant HAp formation in simulated body fluid (SBF) after five days and no cytotoxicity with human mesenchymal stem cells (h-MSC); however after 7 days a reduction in cell viability occurred [37]. A comparative study demonstrated that nBG particles of various sizes (40 -1000 nm) and composition 60% SiO 2 , 36% CaO, and 4% P 2 O 5 supported cell adherence and growth with all particle dimensions [38]. These studies point to the importance of the chemical composition of bioactive glasses, but also to the relevance of nanoparticle size in affecting the regulation of bone cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using sol-gel methodology sub-micron bioactive glass particles (85% SiO 2 , 15% CaO) with a mean particle size of 250 nm demonstrated significant HAp formation in simulated body fluid (SBF) after five days and no cytotoxicity with human mesenchymal stem cells (h-MSC); however after 7 days a reduction in cell viability occurred [37]. A comparative study demonstrated that nBG particles of various sizes (40 -1000 nm) and composition 60% SiO 2 , 36% CaO, and 4% P 2 O 5 supported cell adherence and growth with all particle dimensions [38]. These studies point to the importance of the chemical composition of bioactive glasses, but also to the relevance of nanoparticle size in affecting the regulation of bone cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bioactive ceramic-based polymer nanocomposites have been developed as scaffolds or implants for bone tissue engineering and regeneration. [8][9][10] It is very reasonable and promising by incorporation of BG nanoparticles into a polymer matrix to fabricate bioactive polymer composite biomaterials with controlled physicochemical properties. [5][6][7] BGs have excellent biodegradability, biocompatibility and osteoconductivity, while BG has the ability to form a chemical bonding in contact with living tissue through a bonelike apatite mineral phase.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various forms, bioactive glass particles (BGPs) have attracted much attention due to their light weight, high specific surface area (SSA) and ability to be used as fillers in composites [5][6][7][8][9]. Especially BGPs with hierarchical porous structure are of high interest for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of BGPs with novel morphologies including spheres, worm-like and hollow structures have been synthesized by sol-gel technology [6,16,17]. Gel-derived BGs are intrinsically nano porous and have larger SSA than conventional melt-derived BGs with the same composition, which subsequently enhances the bioactivity and provides the possibility of loading biomolecules [18][19][20].…”
Section: Introductionmentioning
confidence: 99%